Restorative Treatment Considerations for Black Triangle: A Case Series - Yusof, Hazira M.; Abdul Hayei, Nur Ayman (European Journal of General Dentistry, 2023)
The interdental papilla is of utmost importance in smile aesthetics. Missing interdental tissue often raises an aesthetic concern; however, the issue is more than just an aesthetic complication. This study reviews the most commonly seen cases and methods to minimize the aesthetic complications caused by missing interdental tissue. The technique that will be discussed is from nonsurgical techniques, including composite restoration, indirect restorations, and gingival veneer. This article is clinically relevant in educating clinicians on various methods to restore and improve the optics that arise from a missing interdental papilla.
Keywords: black triangle; dental aesthetic; gingival recession; interdental papilla